Iron status and dietary iron intake in relation to overweight/obesity in U.S. adults: a nationwide population-based study - Lin, Yuanyuan; Chen, Yexin; Liu, Jiangteng; Li, Minghao; Tang, Ying; Zhao, Jinxi; Zhang, Yaofu (Frontiers in Nutrition, 2025)
BackgroundEvidence on the associations between iron status biomarkers and both overweight/obesity prevalence and body mass index (BMI) is limited.MethodsThis cross-sectional analysis utilized data from 5,454 participants in the NHANES 2003–2006 and 2017–2020 cycles. Overweight and obesity were defined as BMI ≥ 25 kg/m2 and ≥30 kg/m2, respectively. Weighted multivariable logistic and linear regression models were used to assess associations between iron biomarkers, dietary iron intake, and overweight/obesity risk or BMI. Restricted cubic splines (RCS) were utilized to explore potential non-linear patterns. Furthermore, subgroup analyses stratified by categorical covariates were conducted.ResultsAfter adjusting for confounding variables, weighted logistic regression analysis identified reduced odds of overweight/obesity with higher dietary iron intake (OR = 0.98, p = 0.026), serum iron (SI; OR = 0.98, p = 0.004), and transferrin saturation (TSAT; OR = 0.98, p = 0.003). Weighted multivariable linear regression analysis demonstrated inverse associations of dietary iron intake (β = −0.06, p = 0.045), SI (β = −0.02, p < 0.001), and TSAT (β = −0.09, p < 0.001) with BMI. The total iron-binding capacity (TIBC) exhibited a marginal positive association with overweight/obesity risk and BMI. RCS analysis revealed non-linear dose–response relationships between SI, TSAT, TIBC, and overweight/obesity risk. After Bonferroni correction, no significant interaction effects were observed between iron biomarkers and stratified variables.ConclusionElevated dietary iron intake, serum iron, and TSAT are inversely associated with overweight/obesity risk, highlighting the potential protective role of adequate iron status in preventing obesity.